Increased knowledge about clean and healthy living behavior in an effort to prevent diarrhea - Gustini Gustini; Sumiyati Sumiyati; A.Syamsinar Asmi Asmi; Nordianiwati Nordianiwati; Hendrik Hendrik (Edukasi Ilmiah Indonesia, 2024)
Diarrhea is one of the common public health issues, especially in areas with poor sanitation and unhealthy lifestyles. Preventive efforts against diarrhea involve not only medical interventions but also the importance of education on PHBS (Clean and Healthy Living Behavior). This study aims to evaluate the effectiveness of increasing knowledge about PHBS in preventing diarrhea. The research method used is experimental with a pre-test and post-test control group design. The subjects consist of two groups: the intervention group receiving PHBS education and the control group without education. Data collection was done through knowledge questionnaires before and after the intervention. The results showed a significant increase in knowledge about PHBS in the intervention group after receiving education, compared to the control group. This indicates that PHBS education is effective in improving the knowledge and understanding of the community in preventing diarrhea. The conclusion of this research emphasizes the importance of PHBS education in preventing diarrhea in the community. Structured and comprehensive education programs can be an effective strategy to reduce the incidence of diarrhea and improve public health overall.